Perancangan dan Simulasi Infrastruktur Jaringan Gedung Baru dengan Integrasi ke Data Center Menggunakan Cisco Packet Tracer - Aang Anwarudin; Imam Tri Suryadin; Lazuardi Fatahilah Hamdi (Lembaga Pengembangan Kinerja Dosen, 2025)
The addition of a new building within the Muhammadiyah University of Gombong requires structured and reliable network integration to optimally support technology-based academic activities. This need arises along with the increasing use of information systems, e-learning, and computer-based examination facilities that require high-speed, stable, and secure networks. This study aims to design and simulate the network infrastructure in the new building by connecting it to the data center located in the Pustekom Building as the main network core of the campus. The research method uses a waterfall model approach, which includes the stages of needs analysis, system design, simulation implementation, testing & evaluation, and documentation. The network design adopts a hierarchical topology for inter-building connections, while the local network within the new building uses a star topology that is more efficient and easy to manage. The main focus of development is on the Objective Structured Clinical Examination (OSCE) room on the 3rd and 4th floors that requires stable network support for 40 computer units. Simulations were conducted using Cisco Packet Tracer to test connectivity, VLAN configuration, network segmentation, and structured IP address distribution. The simulation results show that the designed network system can run according to requirements, is integrated with the main campus network, and is able to support complex academic scenarios. This research is expected to serve as a reference for planning and developing similar networks on campuses and other institutions. Future trials on physical implementations are needed to measure actual network performance, add monitoring systems, and strengthen network security to improve system reliability and scalability.